Tingkat Kemampuan Gerak Motorik Kasar Siswa Kelas IV & V Sekolah Dasar Negeri 1 Gulang Kecamatan Mejobo Kabupaten Kudus (Universitas Negeri Semarang, 2022)
Physical growth and motor development can be influenced by several factors, internally and even externally, in physical growth it is clearly seen that there are differences in motor development as well as differences, this occurs according to the physical activities carried out by students. The problem of this research is to “How big is the gross motoric ability of the upper grade students of SD Negeri 1 Gulang, Mejobo District, Kudus Regency